Foreign prisoners in Europe: an analysis of the 2012 Council of Europe Recommendation and its implications for international penal policy - Mulgrew, Roisin (USAK, 2016)
The issue of migration is attracting significant media and political attention in Europe. Migration has been one of the causes of the rapid rise in the number and proportion of foreigners in national prisons. In response to this problem, the Council of Europe’s Committee of Ministers in 2012 adopted a recommendation concerning the treatment of foreign prisoners.